Photo-supported conversations about well-being (BeWellTM) for patients with exhaustion disorders - a controlled clinical intervention study - A. Birgitta Gunnarsson; Petra Wagman; Ulrica Hörberg; Kristina Holmgren; Sara Holmberg (Taylor & Francis Group, 2024)
Introduction Health-promotion approaches to address stress-related exhaustion disorders, reduce personal suffering, improve coping and participation in everyday life are needed in primary care. The aim of this study was to investigate self-reported health and well-being before and after an intervention focusing on well-being with photo-supported conversations (BeWellTM).Material and methods Eighty-one patients (69 women), 20-67 years old, with exhaustion disorders were recruited at Swedish primary health care centres (PHCC) to a controlled clinical study. The intervention group (n = 40) were offered BeWell™ by therapists in addition to care as usual. Controls (n = 41) received only care as usual. The primary outcome, self-rated symptoms of exhaustion (Karolinska exhaustion disorder scale, KEDS), and secondary outcomes, anxiety and depression, sense of coherence, quality of life, occupational balance, and work ability, were assessed by validated questionnaires. Non-parametric statistical analyses were used to compare data collected directly after the treatment period with baseline measures.Results Demographics and self-rated baseline measures of health and well-being were comparable between the groups, apart from sick leave being more common in the intervention group. Participants in the intervention group reduced their level of exhaustion more than the control group (median difference on KEDS −9.0 vs −4.0, p = .035). However, the size of the KEDS reduction was related to baseline KEDS and, not independently associated with group assignment. Both groups improved regarding secondary outcome measures.Conclusion Stress-related symptoms decreased considerably over the treatment period for both groups. The potential benefit of the BeWell™, which was intended to facilitate recovery, needs to be further evaluated.